Olfactory Reception of Host Alarm Pheromone Component by the Odorant-Binding Proteins in the Samurai Wasp, Trissolcus japonicus (Hymenoptera: Scelionidae) - Zhang, Jinping; Zhong, Yongzhi; Tang, Rui; Rebijith, K. B.; Li, Fengqi; Chen, Guohua; Zhang, Feng (Frontiers in Physiology, 2020)
The samurai wasp, Trissolcus japonicus is the predominant egg parasitoid of the brown marmorated stink bug, Halyomorpha halys in its native ranges in China. (E)-2-decenal is a major component of the alarm pheromone of H. halys, an important invasive insect pest with significant economic importance. T. japonicus can be strongly repelled by (E)-2-decenal, and thus it’s host location efficiency would be reduced in the field. Better understanding on the molecular basis of olfactory reception of this host alarm pheromone component by T. japonicus may provide opportunities to develop novel approaches to enhance biological control efficacy of the parasitoid against H. halys. We identified three classical Odorant Binding Proteins (OBPs) from T. japonicus by transcriptome sequencing. Thus, identified OBPs were expressed in a heterologous expression system, harvested, and then challenged with (E)-2-decenal in binding assay experiments. TjapOBP2 showed highest binding ability to (E)-2-decenal, compared to TjapOBP1 and TjapOBP3. Our results unambiguously suggest that TjapOBP2 would play an important role in discriminating (E)-2-decenal and could be a possible target for further intervention in the parasitoid-host system.